Comparison of day wise maturity and failure rates of radio-cephalic and brachiocephalic fistulas using Color Doppler ultrasound in chronic kidney disease patients - Tomar, Shubhendra; Kumar, Dinesh; Sawar, Sameer (International Journal of Research in Medical Sciences, 2025)
Background: Arteriovenous fistula is an autogenous connection between Artery and a vein which is created in patients of chronic kidney disease which need frequent hemodialysis as it allows adequate blood flow during the process and has high patency rates and lower complications. Methods: This prospective study was conducted in tertiary care centre medical college in patients of age group 18-60 yrs. involving both genders with chronic kidney disease and hemodialysis with radio cephalic or brachiocephalic fistula. Results: In our study out of 63 patients in 38 patients radio cephalic fistula was made in (60.3%), brachiocephalic in 11 patients (17.5%) and 14 cases were not fit for the surgery. In a comparison of day wise maturity of brachiocephalic and radio cephalic fistulas the maturity at day 1 for brachiocephalic fistula was ~37% and ~32% for radio cephalic fistulas. On day 14; 8 of the 11 brachiocephalic fistula (72%) and 19 of the 38(50%) of the patients with radio cephalic had maturity. On day 42; 81% of the brachiocephalic fistula and radio cephalic fistula 27(71%) had maturity. Out of 11 total brachiocephalic 9 were mature at the end of study with failure rate of 18.2% and out of the 38-radio cephalic fistula 27 patients were mature with failure rate of 28.9%. Conclusions: In our study involving 63 patients the most common fistula was radio cephalic fistula followed by brachiocephalic fistula, even though the brachiocephalic fistulas had an earlier maturity rate; long term complications of brachiocephalic fistula were more.